An introduction to NSAIDs for cattle: recommendations for the veterinary surgeon. (2nd July 2020) - Laven, Richard
Abstract : non-steroidal anti-inflammatory drugs (NSAIDs) are increasingly used on cattle in the UK. However there is a lack of evidence on which product to use and when to use it. This guide combines published data on the NSAIDs available for cattle in the UK and basic pharmacology, so that veterinarians can make an informed choice when they prescribe NSAIDs for use in cattle.